The Use of a Virtual Reality Training System on Gross Motor Function and Balance in Children with Cerebral Palsy: A Multiple Single-Subject Experimental Report - Antigoni Kolezoi; Alexandra Lepoura; Anna Christakou; Nikolaos Chrysagis; Panagiota Lalou; Vasiliki Sakellari (Applied Sciences)
Cerebral palsy (CP) is a neuromotor disorder affecting movement, muscle tone, and posture, leading to difficulties in motor coordination, balance, and strength. Virtual reality (VR) games offer an interactive method to engage children in a non-real environment, potentially improving balance and motor function. This study aimed to explore the impact of a VR-based balance system on gross motor function and balance in children with CP. Four participants (two boys and two girls, mean age 9.75 ± 3.41) were assessed at three time points: pre-treatment, six weeks post-initial assessment, and two weeks after intervention. Using tools like the Gross Motor Function Measure Scale (GMFMS), Pediatric Balance Scale (PBS), and Gross Motor Performance Measure (GMPM), the study found significant improvements in gross motor skills, balance, and motor performance with the use of the Nintendo Wii Balance Board within conventional physiotherapy. Further research is recommended to refine intervention parameters, incorporate additional outcome measures, and assess broader applicability, including for children with conditions like ADHD.